Minocycline hydrochloride (Minocin) as a single-dose oral treatment of uncomplicated gonorrhoea in men. Issue 1 (February 1976) - Masterton, G; Schofield, C B
Abstract : 349 male patients with uncomplicated gonococcal urethritis were treated with a single dose of 300 mg. or 400 mg. minocycline hydrochloride. The lower dose gave a lower failure rate, 3-2 compared with 5-1 per cent., but this difference was not statistically significant. The overall known failure rate of 4-2 per cent. compares most favourably with our previous findings in this area using other drugs of the tetracycline group. The incidence of post-gonococcal urethritis (5-1 per cent.) was also the lowest we have found. The few side-effects reported were comparatively trivial. Because of its high degree of therapeutic efficacy, the relatively lack of side-effects, and the reduced incidence of post-gonococcal urethritis, minocycline hydrochloride should be considered the drug of choice whenever single-dose oral treatment is given in uncomplicated gonorrhoea in men.